Numerical Simulation of Moving Contact Lines with Surfactant by Immersed Boundary Method (Communications in Computational Physics, 2010)
In this paper, we present an immersed boundary method for simulatingmoving contact lines with surfactant. The governing equations are the incompressibleNavier-Stokes equations with the usual mixture of Eulerian fluid variables and Lagrangianinterfacial markers. The immersed boundary force has two components: onefrom the nonhomogeneous surface tension determined by the distribution of surfactantalong the fluid interface, and the other from unbalanced Young's force at the movingcontact lines. An artificial tangential velocity has been added to the Lagrangianmarkers to ensure that the markers are uniformly distributed at all times. The correspondingmodified surfactant equation is solved in a way such that the total surfactantmass is conserved. Numerical experiments including convergence analysis arecarefully conducted. The effect of the surfactant on the motion of hydrophilic andhydrophobic drops are investigated in detail.